A STUDY ON ASSESSING CONSTRUCTION SITE SAFETY PRACTICES AMONG CLASS OF CONTRACTORS - Ade Asmi; Aurino Djamaris; Ahmad Dasuqi Bin Dahlan (Jurnal Infrastruktur, 2023)
In recent years, this construction area has been considered as one of the most dangerous industries in which workers are more exposed to the risk of accidents. The Department of Occupational Safety and Health (DOSH) statistics prove that the construction industry has the highest rate of fatal accidents compared to other industries in the country. Therefore, this study mainly focused on the implementation of safety practices in construction industry focusing on among class of contractor A, B, C and D. Regarding to this fact, the main goal of this study is focus on the evaluation of the implementation of safety practices among each class of contractors. This study was started by reviewing literature reviews from journals, thesis, articles, books and web pages. Questionnaire surveys were formed and designed focusing on safety practices in the construction industry. A survey in questionnaire form was carried out to obtain data from the contractor’s class A to D. Subsequently, the data from the questionnaire were analyzed by using the SPSS software. In conclusion, this study also could show the difference of level of safety practices which is applied by every class of contractor in their workplace area that class of contractor C and following by class of contractor D, are contractors which is noted the lowest level in practicing safety work culture in construction. The study also proposes some suggestions and recommendations to improve the safety practices and to minimize the accidents at construction industry.